ANALISIS KERUSAKAN UNIVERSAL SHAFT DAN SPINDLE SUPPORT STAND ROLLING MILL AKIBAT VIBRASI - Yanto, Andri (Universitas Muhammadiyah Metro, 2025)
Reinforcing steel and concrete are components commonly used in construction projects for multi-storey buildings, bridges, houses and so on. Reinforcing steel can be made using a rolling or rolling process. In the rolling process, high vibration often occurs, especially in the finishing mill area which works at a speed of 18-21 m/s with a motor rotation of 1000 – 1300 rpm. Damage occurred to the spindle support, stand and missroll (rolling process failure). The expected RMS value of vibration speed is <20mm/s. This research aims to identify the damage that occurs and reduce or dampen the vibrations that occur. The research results show that after 3 (three) repairs were carried out, the first repair was replacing the Universal Joint Shaft, as well as changing the cross joint type to the SWC type and changing the spline design, the second repair was replacing the liner using Shore A95 polyurethane material, the third repair was replacing the ring. Chock Spindle uses shore A 90 polyurethane material. The RMS value of vibration speed can be reduced to between 19.1 – 26.3 mm/s. The main factor that arises from high vibrations is mechanical looseness due to lack of lubrication in machine parts which rub continuously while the machine is rotating.